PERAN KOMUNIKASI KELUARGA ISLAMI DALAM MEMBENTUK GENERASI MUDA BERPRESTASI DAN BERAKHLAK - Syafira Natasya (Universitas Islam Negeri Imam Bonjol Padang, 2025)
The increasingly complex development of the modern era has become a challenge for Islamic families in shaping a young generation that is both excellent and of strong character. Amid the rapid flow of globalization, technological advancement, and social change, families are required to instill firm Islamic values so that children are not influenced by negative environmental factors. This study aims to determine the role of Islamic family communication in shaping young people who are both high-achieving and virtuous. This research employs a literature study method by analyzing the objectives of relevant scientific writings from various credible sources. The data were analyzed using a content analysis approach to examine the forms and roles of Islamic family communication in the process of building children’s character and academic achievement. The results indicate that family communication plays a crucial role. First, as a means of instilling moral and ethical values through advice, exemplary behavior, and the habituation of good conduct in accordance with Islamic teachings. Second, as a spiritual guide that directs children in understanding the values of faith, responsibility, and compassion. Third, as a source of motivation and encouragement for children’s achievement by fostering open, democratic, and empathetic communication. Finally, as a supervisory and controlling tool to help children protect themselves from negative influences. Thus, Islamic family communication serves as a fundamental pillar in developing a young generation that excels in both academic achievement and noble character while behaving in accordance with Islamic principles.